Hypoglycemic and H2O2-induced oxidative injury protective effects and the phytochemical profiles of the ethyl acetate fraction from Radix Paeoniae Alba - Zhang, Lu; Peng, Chun-yan; Wang, Pei-xin; Xu, Linju; Liu, Jia-hui; Xie, Xing; Lu, Ling; Tu, Zong-cai (Frontiers in Nutrition, 2023)
Radix Paeonia Alba (RPA) is often used as food and medicine. This study aimed to enrich and identify the antioxidant and hypoglycemic bioactive compounds from RPA. The results indicated that the ethyl acetate fraction (EAF) showed the highest total phenolic content, DPPH, ABTS+ scavenging ability, and α-glucosidase inhibition ability (IC50 = 7.27 μg/ml). The EAF could alleviate H2O2-induced oxidative stress in HepG2 cells by decreasing the MDA and ROS levels, improving cell apoptosis, increasing the enzyme activity of GPX-Px, CAT, SOD, Na+/K+-ATP, and Ca2+/Mg2+-ATP, and stimulating T-AOC expression, which also enhanced the glucose uptake of insulin-resistant HepG2 cells. In addition, the EAF significantly reduced the fasting blood glucose level and improved glucose tolerance in diabetic mice. An HPLC-QTOF-MS/MS analysis displayed that procyanidin, digallic acid isomer, methyl gallate, tetragalloylglucose isomer, dimethyl gallic acid, and paeoniflorin were the major compounds in the EAF. These findings are meaningful for the application of the EAF in the medicinal or food industry to prevent and treat oxidative stress and diabetes mellitus.